Measuring Competitiveness in Syrian Banking Sector Using Structure and Unstructured Approaches (Journal of Hama University, 2022)
This study aims to analyze and measure the competitiveness in the Syrian banking sector during the period (2008-2018), to achieve this goal, the research used bank concentration ratio (CRK) and the Hirschman Index (HHI) provided by the structural approach, and Panzer-Rose (PR) approach presented by the non-structural approach. An annual panel data was used to reach the value of H- Statistic for Panzer-Rose (PR) for each of the fixed effect model (FEM), random effect model (REM), pooled regression model (PRM) and comparison between them, the result of the comparison shows that the best reliable model to reach the value of H- statistical in Panzer-Rose approach for total returns and return on assets is random effect model. The study concluded that the banking market in Syria is dominated by a state of monopoly by government banks, Where the Commercial Bank of Syria controls more than 70% of this market, according to the concentration ratios, While the Hirschman Index exceeded 1800, Which indicates the high concentration and the prevailing monopoly. as for Panzer-Rose approach, the H-statistical was -0.003 (if the value of the statistic is less than zero, this is evidence of the existence of a monopoly), This state of monopoly is due to the control of public banks as a result of their seniority, the crisis that accompanied the entry of private banks to work at the end of 2011, and the laws and legislations that restricted The ability of private banks to achieve a competitive advantage.
Keywords: competitiveness, concentration ratio (CR3), Hirschman index (HHI), Panzer-Rose method (P-R), pooled regression model, fixed effect model, random effect model.